Achieving the impossible: a review of magic-based interventions and their effects on wellbeing - Wiseman, Richard (PeerJ, 2018)
Research has demonstrated that involvement with mainstream performing arts, such as music and dance, can boost wellbeing. This article extends this work by reviewing little-known research on whether learning magic tricks can have an equally beneficial effect. We first present an historic overview of several magic-based interventions created by magicians, psychologists and occupational therapists. We then identify the potential benefits of such interventions, and review studies that have attempted to systematically assess these interventions. The studies have mostly revealed beneficial outcomes, but much of the work is of poor methodological quality (involving small numbers of participants and no control group), and has tended to focus on clinical populations. Finally, we present guidelines for future research in the area, emphasizing the need for more systematic and better-controlled studies.